A Variational Nodal Approach to 2D/1D Pin Resolved Neutron Transport for Pressurized Water Reactors. (4th May 2017) - Zhang, Tengfei; Lewis, E. E.; Smith, M. A.; Yang, W. S.; Wu, Hongchun
Abstract: A two-dimensional/one-dimensional (2D/1D) variational nodal approach is presented for pressurized water reactor core calculations without fuel-moderator homogenization. A 2D/1D approximation to the within-group neutron transport equation is derived and converted to an even-parity form. The corresponding nodal functional is presented and discretized to obtain response matrix equations. Within the nodes, finite elements in the x-y plane and orthogonal functions in z are used to approximate the spatial flux distribution. On the radial interfaces, orthogonal polynomials are employed; on the axial interfaces, piecewise constants corresponding to the finite elements eliminate the interface homogenization that has been a challenge for method of characteristics (MOC)–based 2D/1D approximations. The angular discretization utilizes an even-parity integral method within the nodes, and low-order spherical harmonics (PN ) on the axial interfaces. The x-y surfaces are treated with high-order PN combined with quasi-reflected interface conditions. The method is applied to the C5G7 benchmark problems and compared to Monte Carlo reference calculations.